Digital Gamification Tool (Let’s Control Flu) to Increase Vaccination Coverage Rates - Lopes, Henrique (2024)
Lopes, H., Baptista-Leite, R., Hermenegildo, C., & Atun, R. (2024). Digital Gamification Tool (Let’s Control Flu) to Increase Vaccination Coverage Rates: Proposal for Algorithm Development. JMIR Research Protocols, 13, 1-17. https://doi.org/10.2196/preprints.55613, https://doi.org/10.2196/55613 --- The authors would like to thank Hans Winberg, Matti Sällberg, Toomas Timpka, and Armin Spreco for their work and contributions to the National Advisory Board for Sweden. The “Let’s Control Flu” project received funding from Sanofi; however, the research was conducted independently of the sponsoring company.